2016
DOI: 10.1097/gme.0000000000000630
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of plasma metabolites in postmenopausal women with metabolic syndrome

Abstract: Objective:The aim of the study was to investigate the associations of amino acids and other polar metabolites with metabolic syndrome (MetS) in postmenopausal women in a lean Asian population.Methods:The participants were 1,422 female residents enrolled in a cohort study from April to August 2012. MetS was defined according to the National Cholesterol Education Program Adult Treatment Panel III modified for Japanese women. Associations were examined between MetS and 78 metabolites assayed in fasting plasma sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 66 publications
1
39
0
Order By: Relevance
“…Biomarker identification is performed in different biological fluids, blood being one of the most promising amongst them. In recent studies, metabolites and especially amino acids were identified as biomarkers in blood for amyotrophic lateral sclerosis , chronic kidney disease (CKD) , major depressive disorder , onchocercias infection , osteoporosis , Parkinson's disease , pancreatic cancer , urinary tract symptoms and metabolic syndrome in postmenopausal women by CZE‐MS. For identification and accurate quantification of biomarkers for inborn errors of metabolism from dried blood spots, DiBattista et al.…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Biomarker identification is performed in different biological fluids, blood being one of the most promising amongst them. In recent studies, metabolites and especially amino acids were identified as biomarkers in blood for amyotrophic lateral sclerosis , chronic kidney disease (CKD) , major depressive disorder , onchocercias infection , osteoporosis , Parkinson's disease , pancreatic cancer , urinary tract symptoms and metabolic syndrome in postmenopausal women by CZE‐MS. For identification and accurate quantification of biomarkers for inborn errors of metabolism from dried blood spots, DiBattista et al.…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…15 Dietary intake was assessed using a food frequency questionnaire. 16 Height and weight were measured with the participant wearing light clothing. Body mass index was calculated as weight in kilograms divided by the squared height in meters.…”
Section: Data and Sample Collectionmentioning
confidence: 99%
“…Hypertension was defined as the use of any antihypertensive drug, systolic bold pressure $140 mmHg, or diastolic blood pressure $90 mmHg. 15,16 Blood samples were collected early in the morning (after the participant had fasted overnight) and then centrifuged to obtain plasma for measuring BCAA levels and serum for measuring lipid levels and other indicators. Plasma BCAA levels were quantified using capillary electrophoresis timeof-flight mass spectrometry (CE-MS) according to a previously reported protocol.…”
Section: Data and Sample Collectionmentioning
confidence: 99%
“…The plasma from 1422 Asian women suffering from metabolic syndrome was analysed. A special focus was placed on AA and polar metabolites . Thirty metabolites were related to metabolic syndrome.…”
Section: Metabolomics Biomedical Studiesmentioning
confidence: 99%